Low-grade fibromyxoid sarcoma of the liver in a pediatric patient: Case report - Karen Juliana Salinas-Castro; Valentina Mejía-Quiñones; Clara Ivette Campos García; Natalia Yeritza Zuñiga-Londoño (Radiology Case Reports)
Malignant liver tumors in children are rare, accounting for only 0.5%-1.5% of all pediatric cancers. Low-grade fibromyxoid sarcoma is an uncommon subtype of malignant fibroblastic neoplasm, typically arising in the deep soft tissues of the trunk and extremities. It primarily affects young adults, and less frequently, children and adolescents. Diagnosis can be challenging due to its deceptively benign histologic appearance. We report the case of a 16-year-old female who presented with nonspecific gastrointestinal symptoms, self-limited fever, mild epistaxis, and scant vaginal bleeding. Imaging studies revealed a hepatic mass located in the right lobe, further characterized by magnetic resonance imaging. The patient underwent partial hepatectomy, and histopathological examination confirmed the diagnosis of low-grade fibromyxoid sarcoma.